2017
DOI: 10.1108/compel-10-2016-0460
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of in-mold electromagnetic stirring process for fluid flow and solidification

Abstract: Purpose The purpose of present investigation is to analyze the in-mold electromagnetic stirring (M-EMS) process and the effect of stirrer frequency on fluid flow and solidification in a continuous casting billet caster mold. Design/methodology/approach A hybrid approach involving finite element and finite volume method has been used for the study. Finite element model is used to calculate time variable magnetic field, which is further coupled with fluid flow and solidification equations for magneto-hydrodyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Wang et al [15] developed a 3-D coupled model considering electromagnetic field, flow field, heat transfer and level fluctuation under different EMS positions in continuous billet mold, and found that the velocity and wave height at steel/slag interface decreases under lower stirrer position. Maurya et al [16][17][18] analyzed the influence of EMS on flow and solidified shell under different EMS currents and frequencies. However, little research considered the influence of EMS on the flow and initial solidification on slab.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [15] developed a 3-D coupled model considering electromagnetic field, flow field, heat transfer and level fluctuation under different EMS positions in continuous billet mold, and found that the velocity and wave height at steel/slag interface decreases under lower stirrer position. Maurya et al [16][17][18] analyzed the influence of EMS on flow and solidified shell under different EMS currents and frequencies. However, little research considered the influence of EMS on the flow and initial solidification on slab.…”
Section: Introductionmentioning
confidence: 99%
“…Maurya et al [17][18][19] investigated the effect of the stirrer width at different currents and frequencies and the stirrer position on the fluid flow and solidification behaviors in a mold using M-EMS. Fang et al [20] and Wang et al [21] developed multiphysical models to predict the effect of the stirrer position on the magnetic field distribution, fluid flow streamlines, temperature distribution, inclusion removal, solute diffusion, mold-level fluctuation, and slag entrapment behavior.…”
Section: Doi: 101002/srin202200796mentioning
confidence: 99%
“…To account for the impact of the magnetic field on the fluid flow, Lorentz force derived in Equation ( 6) has been added to the standard Navier-Stokes equation, as shown in equation (13). Because of the decreased porosity during solidification, the mushy zone's momentum decreases.…”
Section: Fluid Flow Equationsmentioning
confidence: 99%
“…Equations ( 15) and ( 16), which indicate the solutions for the governing differential equations for turbulent kinetic energy (k) and dissipation rate ( ), respectively: To verify the correctness of the model, they have been validated individually for the magnetic field and solidification model. The detailed validation has been reported by Maurya and Jha [13]. A comparison of fluid flow with and without M-EMS has been done in order to investigate the EMS process.…”
Section: ( ⃗⃗⃗ ⃗⃗⃗ )mentioning
confidence: 99%